2004
DOI: 10.1196/annals.1307.044
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Bovines with Concealed Antigens from Haematobia irritans

Abstract: To evaluate an immunization procedure using antigens from Haematobia irritans intestine (AgHiI), four bovines (group I) were inoculated with AgHiI mixed with Freund's incomplete adjuvant containing Lactobacillus casei, three bovines (group II) received AgHiI, and three bovines (group III) received saline solution. At day 35, blood was collected from each animal to feed H. irritans flies. There was no difference in the fly mortality observed in the three groups. The percentage of reduction of eggs oviposited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…4). However, only Breijo et al [16] showed a direct effect on fly infestation as a result of vaccination, while the other studies reported only a reduced number of eggs [13] or reduced blood intake and delayed ovarian development [14,15], but no direct negative effects on fly mortality, as also observed in the present study (Table 3).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…4). However, only Breijo et al [16] showed a direct effect on fly infestation as a result of vaccination, while the other studies reported only a reduced number of eggs [13] or reduced blood intake and delayed ovarian development [14,15], but no direct negative effects on fly mortality, as also observed in the present study (Table 3).…”
Section: Discussionsupporting
confidence: 67%
“…To the best of our knowledge, attempts to develop an anti-horn fly vaccine have been restricted to studies with crude antigens extracted from the horn fly's gut, recombinant thrombostasin (an anti-clotting protein found in horn fly saliva), and hematobin (a salivary gland protein) [13][14][15][16]. These studies have shown that vaccination of cattle with crude or recombinant antigens induces a specific and significant IgG response, similar to what we found in the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less research has been reported for biting flies though Bautista et al (2004) recently reported that vaccination of cattle with gut antigens from the horn fly Haematobia irritans irritans reduced egg production by between 11 and 29 % in flies fed on the blood of vaccinated animals, the difference depending on adjuvant and/or antibody titre. In addition, vaccination of cattle and rabbits with recombinant thrombostatin, a thrombin inhibitor, reduced blood uptake by flies feeding on hosts sensitized by prior exposure to the parasite as well as inhibiting egg development (Cupp et al 2004).…”
Section: N S E C T P a R A S I T E Smentioning
confidence: 99%
“…Esto sugiere un efecto modulador de los antígenos en las glándulas salivales de H. irritans (86) . En otro estudio se encontró una correlación entre la reducción de huevos y los niveles de anticuerpos contra H. irritans alimentadas con sangre de bovinos inmunizados con antígenos de intestino de moscas; sin embargo, la mortalidad de moscas alimentadas de animales inmunizados no fue significativa (87) .…”
Section: Control Alternativounclassified